Dynamic Susceptibility Spectra of Stadium-Shaped and Elliptical Nanostructures - Escrig-Murua, J; Saavedra-Díaz, E (Elsevier B.V., 2022)
We investigated the dynamic susceptibility in the absence of a bias field of stadium-shaped and elliptical nanostructures by micromagnetic simulations. Both the resonant frequencies and the number of peaks depend on the minimum energy configuration, which in turn is a function of the aspect ratio of the system. Dynamic susceptibility does not vary much if the nanostructure is stadium-shaped or elliptical, if its lowest energy state is a vortex. If the configuration is a saturated state, the low resonance frequency is only visible in stadium-shaped nanostructures and not in elliptical nanostructures, which is justified by the impact of the curvature of each nanostructure. The possibility of controlling frequencies by modifying the geometric parameters of the system suggests the possibility of using these nanostructures in potential magnetic controllable frequency devices. © 2021 Elsevier B.V.